ANALISIS FRAMING PEMBERITAAN PERMENDIKBUD TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI DI MEDIA ONLINE - Avian Savitri, Lulu; Manalu, S. Rouli; Hasfi, Nurul (Interaksi Online, 2024)
Permendikbud No. 30 of 2021 reflects the government's commitment to preventing and handling sexual violence in universities. However, its implementation triggered debates in various aspects such as religion, socio-culture, and law. Detik.com and Kumparan.com are examples of online media that provide a forum for public discussion on controversial issues related to the regulation. By applying constructivist framing analysis, this study reveals three frames used by online media Detik.com and Kumparan.com, namely "Permendikbud No. 30 of 2021 Upholding Human Rights", "Permendikbud No. 30 of 2021 is a Rudimentary Legal Provision", and "Legalization of Free Sex and increasing the number of LGBT in Permendikbud No. 30 of 2021". Research finds that the media has divided public opinion into three groups such as opponents, moderates, and supporters based on their respective ideological differences. The analysis also highlights the media's dominant focus on religious and legal themes, emphasizing the views of religious figures and referring to Islamic concept and legal prohibitions related to sex outside marriage.